Characteristics of cardiovascular risk factors in an urban and rural population of the Peruvian jungle - July, 2014 - Martínez-Espichán, Yordan (2017)
Objective: To determine the characteristics of the place of residence and the cardiovascular risk factors in a Peruvian jungle population in July 2014. Materials and methods: A descriptive cross-sectional study conducted in individuals between 30 and 74 years old without a diagnosis of or treatment for a cardiovascular disease in an urban and rural population of the district of Yantaló. The sample was obtained using the Power Analysis and Sample Size Software (PASS) program, and consisted of 268 people (152 urban and 116 rural residents). The studied factors were hypertension (HBP), diabetes mellitus (DM), body mass index (BMI), waist-hip ratio (WHR) and smoking. Results: The urban population had higher rates of hypertension (18.4%), while the other risk factors showed no significant differences between the two populations. Conclusions: The only risk factor that showed a significant association with the place of residence was hypertension. In contrast, the other risk factors of the study showed no differences between the two populations, which demonstrates that the district of Yantaló is involved in a process of epidemiological transition due to urbanization.